1063. Healthcare Utilization and Opportunities for HCV Testing and Treatment among Persons under Community Supervision in Pawtucket, RI. (31st December 2020) - Dickerson, Collin; Patry, Emily J; Bazerman, Lauri; Martin, Johanna; Moody, Marc; Beckwith, Curt
Abstract: Background: The burden of hepatitis C virus (HCV) is disproportionately borne by persons involved with the justice system. To explore missed opportunities for HCV screening and treatment among a justice-involved population, we examined healthcare utilization and prior opportunities for HCV testing and treatment among persons under community supervision enrolled in an HCV testing and linkage to care study in Rhode Island (RI). Methods: Two hundred and fifty individuals under community supervision were recruited from an RI probation and parole office. Participants underwent a rapid HCV antibody test (OraSure Technologies) and a baseline survey, which queried participants on justice involvement, demographics, substance use, healthcare utilization and prior HCV testing. A positive HCV antibody test and no report of previous HCV testing was classified as a missed opportunity for testing. Self-reported prior HCV diagnosis with no history of treatment was classified as a missed opportunities for HCV treatment. Results: Forty-five participants (18%) had reactive antibody tests. Of those 45, twenty-five (55%) reported previously being diagnosed with HCV, including thirteen who reported an HCV diagnosis over 10 years ago; none had received HCV treatment. In addition, 135 participants (61.1%) reported previously being tested for HCV; the most common site of prior testing was in jail/prison (n=87). Ten participants had missed opportunities for HCV testing, and 25 had missed opportunities for HCV treatment. Of participants with these missed opportunities, 97% had health insurance, 74% had been to a primary care provider in the past year, and 91% had ≥ 1 identifiable risk factor for HCV. Flowchart of HCV Antibody Test Results and History of HCV Testing Healthcare Utilization among Persons with Missed Opportunities Conclusion: Screening for HCV at community supervision sites is an underutilized venue for HCV screening that can identify previously-undiagnosed HCV infections. Many persons under community supervision are aware of their HCV positive status but have never received treatment. Despite involvement in healthcare systems and adequate health insurance coverage, many patients with risk factors for HCV have not been tested for HCV or have only been tested for HCV while incarcerated. Investing in and implementing strategies to increase testing for HCV is necessary to maximize the care continuum in this priority population. Disclosures: All Authors : No reported disclosures